PERANCANGAN PROTEKSI KEBAKARAN AKTIF PADA BANGUNAN PERGUDANGAN MENGGUNAKAN STANDAR NFPA DAN SNI - Rosyidiin, Afrigh Fajar; Puteri, Agatha Hannabel Avnanta; Priyangga, Dharu Zastia; Ivander, Davin Danny; Liwaq, Moch. Isabil (Airlangga Journal of Innovation Management, 2024)
In the operational conduct of a company, especially those relating to the storage of materials and goods in warehouses, the occupational health and safety OHS) aspects are critical factors that cannot be neglected. Fire was one of the consequences of a non-standard OHS application. The purpose of this research was to provide a proposal for the design of fire protection systems in the Archives and Documents Company, which are light fire extinguishers, sprinkler systems, hydrants, and reservoirs. This research method is observational-descriptive. In conceptual planning, layout, and coordination with the company, the researchers directly perform observations on the PT Archives and Documents to analyze and identify the deficiencies of fire protection equipment owned by the associated companies. ADC requires a total of 9 light fire extinguishers, 192 sprinkler points, 6 hydrants, and a reservoir size of 343,000 liters as a fire protection system according to the National Fire Protection Association standards (NFPA). All buildings that are occupied by humans and have a risk of fire must be equipped with fire protection. for future research in the field of fire safety research to design an emergency response plan for a building by simulating it with advanced technology. By implementing the proposed fire protection, the Company can prevent fire and spread of fire more widely